Bilateral Motor Cortex tDCS Effects on Post-Stroke Pain and Spasticity: A Three Cases Study - Molero-Chamizo, Andrés; Salas Sánchez, Ángeles; Álvarez Batista, Belén; Cordero García, Carlos; Andújar Barroso, Rafael; Rivera-Urbina, G. Nathzidy; Nitsche, Michael A.; Alameda Bailén, José R. (Frontiers in Pharmacology, 2021)
Stroke patients frequently suffer from chronic limb pain, but well-suited treatment approaches have been not established so far. Transcranial direct current stimulation (tDCS) is a safe and non-invasive brain stimulation technique that alters cortical excitability, and it has been shown that motor cortex tDCS can reduce pain. Some data also suggest that spasticity may be improved by tDCS in post-stroke patients. Moreover, multiple sessions of tDCS have shown to induce neuroplastic changes with lasting beneficial effects in different neurological conditions. The aim of this pilot study was to explore the effect of multiple anodal tDCS (atDCS) sessions on upper limb pain and spasticity of stroke patients, using a within-subject, crossover, sham-controlled design. Brain damage was of similar extent in the three patients evaluated, although located in different hemispheres. The results showed a significant effect of 5 consecutive sessions of atDCS, compared to sham stimulation, on pain evaluated by the Adaptive Visual Analog Scales -AVAS-, and spasticity evaluated by the Fugl-Meyer scale. In two of the patients, pain was completely relieved and markedly reduced, respectively, only after verum tDCS. The pain improvement effect of atDCS in the third patient was considerably lower compared to the other two patients. Spasticity was significantly improved in one of the patients. The treatment was well-tolerated, and no serious adverse effects were reported. These findings suggest that multiple sessions of atDCS are a safe intervention for improving upper limb pain and spasticity in stroke patients, although the inter-individual variability is a limitation of the results. Further studies including longer follow-up periods, more representative patient samples and individualized stimulation protocols are required to demonstrate the efficacy and safety of tDCS for improving limb symptoms in these patients.